A pilot clinical trial testing topical resiquimod and a xenopeptide as immune adjuvants for a melanoma vaccine targeting MART-1. Issue 4 (August 2019) - Block, Matthew S.; Nevala, Wendy K.; Pang, Yuan-Ping; Allred, Jacob B.; Strand, Carrie; Markovic, Svetomir N.
Abstract : A vaccine that could expand melanoma-specific T cells might reduce the risk of recurrence of resected melanoma and could provide an alternative or adjunct to standard immunotherapy options. We tested the safety and immunogenicity of a vaccine coupling a melanoma-associated peptide with a xenogenic peptide (to promote epitope spreading) and/or resiquimod (to activate antigen-presenting cells). HLA-A2-positive patients with resected stage II, III, and IV melanoma were assigned to treatment on one of three schedules. All patients received three subcutaneous doses of the peptide MART-1a mixed with Montanide. In addition, patients on schedule 1 received the xenoantigen peptide Gag267–274, patients on schedule 2 received topical resiquimod, and patients on schedule 3 received both Gag267–274 and resiquimod. Blood samples were tested for the frequency of antigen-specific T cells by tetramer assay, as well as immune cell subtypes and plasma cytokine levels. Patients enrolled from October 2012 to December 2014, with 10 patients enrolling to each schedule. The most common adverse events were injection site reaction (26 patients) and fatigue (15 patients). Tetramer analysis revealed antigen-specific responses (defined as doubling of MART-1a-specific T cells from pretreatment to post-treatment) in 20, 60, and 40% of patients treated on schedules 1, 2, and 3, respectively. Vaccine treatment consisting of MART-1a peptide, Gag267–274, Montanide, and topical resiquimod was well-tolerated. The addition of the Gag267–274 xenoantigen was not associated with an increase in the response to MART-1a, whereas use of topical resiquimod was associated with a higher frequency of MART-1a-specific T-cell responses that did not meet statistical significance. Abstract : Supplemental Digital Content is available in the text.